Comparison of Genetic Algorithms and Other Classification Methods in the Diagnosis of Female Urinary Incontinence - Laurikkala, J.; Juhola, M.; Lammi, S.; Viikki, K. (Methods of Information in Medicine, 1999)
Galactica, a newly developed machine-learning system that utilizes a genetic algorithm for learning, was compared with discriminant analysis, logistic regression, k-means cluster analysis, a C4.5 decision-tree generator and a random bit climber hill-climbing algorithm. The methods were evaluated in the diagnosis of female urinary incontinence in terms of prediction accuracy of classifiers, on the basis of patient data. The best methods were discriminant analysis, logistic regression, C4.5 and Galactica. Practically no statistically significant differences existed between the prediction accuracy of these classification methods. We consider that machine-learning systems C4.5 and Galactica are preferable for automatic construction of medical decision aids, because they can cope with missing data values directly and can present a classifier in a comprehensible form. Galactica performed nearly as well as C4.5. The results are in agreement with the results of earlier research, indicating that genetic algorithms are a competitive method for constructing classifiers from medical data.
Keywords: Urinary Incontinence; Computer-Assisted Diagnosis; Genetic Algorithms; Machine Learning; Comparison